Functional Approach in Translating Children's Short Stories from English to Indonesian - Antoni Kurniawan, Natanael; Fitriani, Enis; Setiyo Astuti, Endang (Universitas Insan Budi Utomo, 2024)
This study aims to examine the application of the functional approach in translating children's short stories from English to Indonesian, focusing on the translation of The Big Guest by Shankar into Tamu Besar. The functional approach emphasizes preserving the communicative purpose and cultural relevance of the original text while adapting it to the target audience, young readers in Indonesia. This process involves key elements such as simplifying language, cultural domestication, and emotional adaptation to make the story more accessible and relevant to Indonesian readers. The approach prioritizes balancing fidelity to the original text with necessary cultural modifications to ensure that the story’s message reaches the audience in the most effective way. The results show that applying the functional approach in this translation bridges the cultural gap between the source world and the target audience, ensuring readability for young readers. This study also demonstrates how translated children's literature can serve as a bridge to foster understanding and empathy for other cultures. The functional approach proves crucial in making children's literature more engaging, relevant, and meaningful across cultures.